The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1095/biolreprod50.3.643
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Gonadotropin-Releasing Hormone (GnRH) Binding Sites and Compounds with GnRH-Like Activity in the Ovary of African Catfish, Clarias Gariepinus1

Abstract: GnRH binding was characterized in the African catfish ovary by use of an analog of salmon GnRH (sGnRH- ; [D-Arg6, Trp7, Leu8, Pro9-NEt]-GnRH) as a labeled ligand. Binding of sGnRH-A to catfish ovarian membrane preparation was found to be saturable, displaceable, reversible, and dependent on time, temperature, and tissue concentration. Optimal binding was achieved after 70 min of incubation at room temperature (approximately 22 degrees C) at pH 7.6. Addition of unlabeled sGnRH-A displaced the bound 125I-sGnRH-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Indeed, the presence of a GnRH-like factor has been demonstrated in the African catfish (Habibi et al 1994) and goldfish ovary (Pati & Habibi 1998). However, it is improbable that GnRH would stimulate GtH II secretion but inhibit that of GtH I.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the presence of a GnRH-like factor has been demonstrated in the African catfish (Habibi et al 1994) and goldfish ovary (Pati & Habibi 1998). However, it is improbable that GnRH would stimulate GtH II secretion but inhibit that of GtH I.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, however, the early eluting compound with GnRH-like activity could not be identified, suggesting the presence of either a novel form of GnRH or a GnRH variant resulting from differential splicing of GnRH transcripts (Pati and Habibi, 1998;Nabissi et al, 2000). The presence of compounds with GnRH-like activity was also demonstrated in the ovary of African catfish (Habibi et al, 1994) and seabream (Nabissi et al, 1997). In spite of extensive attempts to purify GnRH peptides from the ovary, cGnRH-II peptide, which is present in the goldfish brain, was not detected in goldfish ovarian extracts suggesting that cGnRH-II expression in the ovary of this species is either very low or transient.…”
Section: Endocrine and Paracrine Regulation Of Synchronized Folliculamentioning
confidence: 74%
“…The latter is a relatively new hypothesis, which is based on recent studies carried out in goldfish and seabream. In this regard, there is unambiguous evidence demonstrating the presence of GnRH and GnRH-R in the gonadal tissue of fish and other vertebrate species (Pati and Habibi, 1992Habibi et al, 1994Habibi et al, , 2001Gazourian et al, 1997;Nabissi et al, 1997). Further studies have provided strong support for the hypothesis that locally produced GnRH plays an autocrine/paracrine role in the regulation of gonadal function.…”
Section: Endocrine and Paracrine Regulation Of Synchronized Folliculamentioning
confidence: 96%
See 1 more Smart Citation
“…Among vertebrates, the presence of GnRH I-receptor has previously been demonstrated mainly in the ovaries of several species of fishes: African catfish, Clarias gariepinus (Habibi et al 1994), sea bream, Sparus aurata (Nabissi et al 1997), goldfish, Carassius auratus (Pati & Habibi 1998) and a teleost, Fugu rubripes (Moncaut et al 2005). The presence of GnRH I-receptor in the vertebrate ovary suggests that GnRH I acts through a receptormediated process (Schirman-Hildesheim et al 2005).…”
Section: Gnrh I and Bradykinin In The Ovariesmentioning
confidence: 99%